2022
DOI: 10.3389/fcimb.2022.954581
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cGAS/STING signaling and corresponding immune escape strategies of viruses

Abstract: Innate immunity is the first line of defense against invading external pathogens, and pattern recognition receptors (PRRs) are the key receptors that mediate the innate immune response. Nowadays, there are various PRRs in cells that can activate the innate immune response by recognizing pathogen-related molecular patterns (PAMPs). The DNA sensor cGAS, which belongs to the PRRs, plays a crucial role in innate immunity. cGAS detects both foreign and host DNA and generates a second-messenger cGAMP to mediate stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 229 publications
1
10
0
Order By: Relevance
“…Our data from cancer cell cultures confirm, indeed, that Pxl promotes a cGAS-STING pathway-dependent proinflammatory cascade, but they also show that Pxl treatment induces a strong upregulation of the PD-L1 protein in cancer cells in a cGAS-STING pathway-dependent manner (see Figures 3 , 4 ). These observations are consistent with the view that negative feedbacks regulate the inflammatory response and with notion that the inflammatory response may have opposite effects on cancer development ( 20 , 31 ). Indeed, the upregulation of PD-L1 expression by cancer cell is believed to substantially contribute to cancer cell resistance to immunosurveillance and to promote cancer cell growth and migration in an auto/paracrine manner as well ( 32 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data from cancer cell cultures confirm, indeed, that Pxl promotes a cGAS-STING pathway-dependent proinflammatory cascade, but they also show that Pxl treatment induces a strong upregulation of the PD-L1 protein in cancer cells in a cGAS-STING pathway-dependent manner (see Figures 3 , 4 ). These observations are consistent with the view that negative feedbacks regulate the inflammatory response and with notion that the inflammatory response may have opposite effects on cancer development ( 20 , 31 ). Indeed, the upregulation of PD-L1 expression by cancer cell is believed to substantially contribute to cancer cell resistance to immunosurveillance and to promote cancer cell growth and migration in an auto/paracrine manner as well ( 32 ).…”
Section: Discussionsupporting
confidence: 92%
“…The phosphorylated forms of STING and IRF3 tended to decline at 8 nM relatively to 4 nM Pxl treatment ( Figure 2 ; see quantitative graphs of the phosphorylated forms). We do not have an exact explanation for this phenomenon, but we believe that it may possibly indicate that negative feedbacks, that attenuate excess proinflammatory signals, are initiated at the highest Pxl concentration ( 20 ).…”
Section: Resultsmentioning
confidence: 97%
“…DNA sensors belong to PRRs. DAI is the first reported cytosolic DNA sensor that contributes to the recognition of multiple types of nucleic acids and enhances the innate immune response by driving inflammatory signaling and a form of inflammatory cell death known as PANoptosis ( 21 24 ). It has been reported that DAI plays a crucial role in the maturation and activation of DCs during viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of cGAMP and STING leads to its transfer from the endoplasmic reticulum to the Golgi apparatus, which is activated by palmitoylation on Cys88 and Cys91 ( 28 , 36 ). TBK1 was recruited onto the conservative PLPLRT/SD motif at the C-terminal tail of STING ( 48 ), and IFIT3 was used as the linker connecting TBK1 and STING ( 36 ). Ligand binding and STING oligomerization seem to promote the trans phosphorylation of TBK1.…”
Section: Biological Characteristics Of Cgas-sting Pathwaymentioning
confidence: 99%